2021
DOI: 10.1038/s41467-021-22116-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lattice distortions driven by surface trapping in semiconductor nanocrystals

Abstract: Nonradiative processes limit optoelectronic functionality of nanocrystals and curb their device performance. Nevertheless, the dynamic structural origins of nonradiative relaxations in such materials are not understood. Here, femtosecond electron diffraction measurements corroborated by atomistic simulations uncover transient lattice deformations accompanying radiationless electronic processes in colloidal semiconductor nanocrystals. Investigation of the excitation energy dependence in a core/shell system show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…We note that analogous concerns are expected for ultra-small 0D semiconductor materials where few atoms experience a bulk-like environment, particular given the possibility that defect states 49 involving surface reconstruction are involved in the photophysics. 99 Thus, there is an opportunity to extend this theoretical framework to capture such complex chromophores, especially where their unique properties may aid applications. In this effort, the thermodynamic quantities that we estimate for the product state resulting from photoexcitation of ultra-small PbS QDs (by characterizing its equilibrium with a molecular spin-triplet exciton with well-dened energy) may offer an intriguing opportunity for testing and calibration.…”
Section: Resultsmentioning
confidence: 99%
“…We note that analogous concerns are expected for ultra-small 0D semiconductor materials where few atoms experience a bulk-like environment, particular given the possibility that defect states 49 involving surface reconstruction are involved in the photophysics. 99 Thus, there is an opportunity to extend this theoretical framework to capture such complex chromophores, especially where their unique properties may aid applications. In this effort, the thermodynamic quantities that we estimate for the product state resulting from photoexcitation of ultra-small PbS QDs (by characterizing its equilibrium with a molecular spin-triplet exciton with well-dened energy) may offer an intriguing opportunity for testing and calibration.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lindenberg et al utilized femtosecond electron diffraction measurements to monitor lattice distortions upon photoexcitation of CdSe nanocrystals and CdSe/CdS core/shells (Guzelturk et al, 2021).…”
Section: Surface Trappingmentioning
confidence: 99%
“…Recently, Lindenberg et al. utilized femtosecond electron diffraction measurements to monitor lattice distortions upon photoexcitation of CdSe nanocrystals and CdSe/CdS core/shells ( Guzelturk et al., 2021 ). Changes in relative diffraction intensity over time were attributed to localized structural deformations caused by hot charge carriers distorting the nanocrystal lattice (i.e.…”
Section: Carrier Dynamics In Semiconductor Nanocrystalsmentioning
confidence: 99%
“…For example, localized trap states at surfaces or interfaces due to atomic defects are ubiquitous in experimental studies of NCs, where they are observed to rapidly quench photoluminescence and result in significantly lower quantum yields. 86,87 An atomistic description of the NC structure allows for the introduction of site-specific defects or alloying to understand their roles in trap formation and to determine the dynamics of trapping in NC systems. 28,88 In addition to the static deformation of the crystal lattice, the effects of lattice fluctuations (i.e., phonons) play a key role in the physics of NCs and must be properly incorporated.…”
Section: Model Hamiltonianmentioning
confidence: 99%